IMPACT OF EFFECTIVE LEADERSHIP STYLE ON PEACE AND DEVELOPMENT IN NIGERIA (Abuja Journal of Sociological Studies, 2026)
Effective leadership is very important in promoting peace and development in Nigeria. This abstract examines the influence of leadership styles on these essential elements of the country's advancement. Given Nigeria's varied ethnic and religious composition, it is imperative to adopt inclusive and transformational leadership strategies. It is undeniable that the leadership of any community or organization sets the pace for peace and development within it. Although progress in any society is a collaborative effort between leaders and followers, the onus of creating the conditions for this collaboration largely falls on the leadership present at that time. It is no surprise that leaders are often held accountable, either positively or negatively, for events occurring during their tenure. Through an exploratory lens, this paper posits that the pursuit of peace and development in Nigeria is closely tied to the demeanour of its leadership, as peace emerges from well-crafted leadership that promotes growth and development. The paper concludes that for Nigeria to achieve peace and substantial development, it must cultivate effective leadership capable of mobilizing and effectively utilizing its significant potential. Authoritarian or divisive leadership intensifies existing conflicts, obstructing development and inciting discord. In contrast, visionary and participatory leadership styles foster unity, promote collaboration, and support sustainable development efforts. The paper therefore contends that Nigeria's advancement depends on nurturing leaders who emphasize inclusivity, transparency, and the collective welfare of the nation, thereby creating an environment that is favourable for both peace and development.